Experimental research of mass transfer in a stabilized foam layer - Moiseev, Viktor; Manoilo, Eugenia; Khukhryanskiy, Oleg; Repko, Kalif (PC Тесhnology сеntеr, 2021)
The object of research: mass transfer processes on a combined contact element in a column apparatus. Investigated problem: determination of the regularities of process parameters in the processing of gas-liquid systems in a foam layer, as well as to interpret the obtained experimental data. The problem of processing industrial gas flows is solved by conducting the process in an intensive mode. The main scientific results: as a result of the study, the regularities of ammonia absorption were revealed depending on the main parameters of the experiment: gas velocity in the column cross-section, ammonia concentration, free cross-section of the combined contact element, and liquid loads. The process of mass transfer in the gas phase is significantly influenced by hydrodynamic parameters – the gas velocity in the apparatus and the specific load on the liquid, which indirectly affect the height of the liquid layer on the plate and the gas content of the layer. The area of practical use of the research results: sorption processes for processing gases and liquids in technological processes, absorption of harmful substances in the treatment of gas emissions. Innovative technological product: new block poppet-nozzle contact device that operates in a stabilized hydrodynamic mode; new ball-shaped weighted nozzle for three-phase foam layer. Scope of application the innovative technological product: technological processes in the treatment of gas emissions or technological gases.
Keywords: industrial gas emissions; cleaning process; mass transfer; foam layer apparatus; foam layer; research of purification processes; stabilization of foam layer; intensive apparatus